PENGUATAN DESA BAUMATA BARAT SEBAGAI DESA PENYANGGA PENGHASIL PROTEIN HEWANI TELUR - Setyani, Ni Made Paramita; Pradana, I Putu Yoga Bumi; Sabat, Diana Meliani (Universitas Padjadjaran, 2026)
Baumata Barat Village holds significant potential as a buffer zone for regional food security through the production of laying hen eggs by the Ora et Labora Farmer Group. However, high feed costs, due to the underutilization of locally available resources, remain a major constraint. This community engagement program aimed to enhance the capacity of the farmer group by promoting the use of locally sourced feed ingredients such as maize. A Participatory Action Research (PAR) approach was employed, encompassing the stages of preparation, socialization, training, technology application, mentoring, and evaluation. The training focused on the formulation of alternative feed using local maize, wheat bran, commercial concentrate, and limestone flour. Program evaluation was conducted using pre- and post-tests to assess changes in knowledge, skills, motivation, and participant satisfaction. Results indicated substantial improvements in knowledge (49.28%), skills (45.25%), motivation (59.48%), and satisfaction (15.37%). These findings demonstrate the effectiveness of the participatory approach in transferring knowledge, enhancing practical competencies, and boosting participant engagement. This program is expected to make a sustainable contribution to food security by strengthening the capacity of local farmers to produce laying hen eggs at lower costs. The utilization of local resources such as maize as an alternative feed ingredient not only reduces dependency on commercial feed but also fosters self-reliance and sustainability in poultry farming in Baumata Barat Village. With the improvement of farmers’ knowledge, skills, motivation, and satisfaction, the productivity and stability of egg production are anticipated to increase, thereby reinforcing the village’s role as a buffer zone for regional food security. Desa Baumata Barat memiliki potensi besar sebagai desa penyangga ketahanan pangan melalui produksi telur ayam ras oleh Kelompok Peternak Ayam Petelur Ora et Labora. Namun, tingginya biaya pakan akibat belum optimalnya pemanfaatan sumber daya lokal menjadi hambatan utama. Kegiatan pengabdian ini bertujuan meningkatkan kapasitas kelompok peternak dalam memanfaatkan potensi lokal seperti jagung untuk pakan alternatif ayam petelur jenis Isa Brown. Metode yang digunakan adalah Participatory Action Research (PAR), meliputi tahapan persiapan, sosialisasi, pelatihan, penerapan teknologi, pendampingan, dan evaluasi. Pelatihan difokuskan pada pembuatan ransum berbahan jagung lokal, dedak gandum, konsentrat, dan tepung kapur. Evaluasi dilakukan dengan pre-test dan post-test untuk mengukur perubahan pada empat aspek: pengetahuan, keterampilan, motivasi, dan kepuasan mitra. Hasil menunjukkan peningkatan signifikan pada pengetahuan (49,28%), keterampilan (45,25%), motivasi (59,48%), dan kepuasan mitra (15,37%). Temuan ini menunjukkan bahwa pelatihan berbasis potensi lokal dengan pendekatan partisipatif efektif dalam meningkatkan kapasitas kelompok serta mendukung keberlanjutan usaha peternakan. Kegiatan ini berpotensi memberikan kontribusi berkelanjutan bagi ketahanan pangan melalui penguatan kapasitas peternak lokal dalam memproduksi telur ayam ras dengan biaya lebih efisien. Pemanfaatan sumber daya lokal seperti jagung sebagai bahan baku pakan alternatif tidak hanya menurunkan ketergantungan terhadap pakan komersial, tetapi juga mendorong kemandirian dan keberlanjutan usaha peternakan di Desa Baumata Barat. Dengan meningkatnya pengetahuan, keterampilan, motivasi, dan kepuasan peternak, diharapkan terjadi peningkatan produktivitas dan stabilitas produksi telur, yang pada gilirannya memperkuat peran desa sebagai penyangga ketahanan pangan regional.